Teacher Competency in Applying Assessment for Islamic Education Learning in the Digitalisation - Mistiawati , Eka Nur; Inayati, Nurul Latifatul; Valarthodi , Mohamed Iyas; Irshad , I (Universitas Muhammadiyah Surakarta, 2025)
The era of digitalisation has transformed the learning assessment process, especially in Islamic Religious Education (PAI). Teachers’ competence in carrying out assessments integrating digital technology with Islamic values is a determining factor in the effectiveness of learning evaluation. This study aims to analyse teachers' competence in conducting Islamic Education learning assessments, identify effective assessment criteria, and examine the implementation of Islamic Education assessments in the digital era. This research uses a descriptive qualitative approach with a phenomenological method, using data collection techniques through interviews, observation and documentation at SMP Muhammadiyah PK Kotabarat Surakarta. PAI teachers’ competence in assessment still needs continuous strengthening. The implementation of Computer-Based Tests (CBT) for PAI shows a significant transformation in the evaluation process, although it still faces technical and pedagogical challenges. The school implemented a comprehensive strategy to address teachers' competency gaps through periodic evaluations, deliberation forums, and continuous training. Developing teachers’ competencies in PAI assessment in the digital era requires the integration of pedagogical, technological and analytical skills supported by continuous professional development programs.